The effect of colloidal aggregates on fat crystal networks - Chauhan, R (2017)
The effect of fumed silica aggregates on fat crystal networks is studied using a combination of rheology, differential scanning calorimetry and polarized light microscopy. We probe a model system for fat-structured foods with the aim of reducing the amount of fat whilst retaining the desirable mechanical and thermal properties. We begin with oscillatory rheology to investigate the effect of added silica and different fat concentrations on the resulting gel networks. The addition of silica is shown to increase the linear viscoelastic region, without significantly changing the storage modulus within this region. Differential scanning calorimetry measurements show that the presence of silica slightly increases the crystallization temperature but does not act as a seed for nucleation or significantly affect the melting profile of the system. We propose the formation of a composite gel network structure with a layer of silica on the surface of the fat crystal chains. We demonstrate that it is possible to create reduced-fat alternatives with similar rheological behaviour and thermal properties as the full-fat systems through the addition of colloidal silica. Next, we look at the effects of silica concentration, surface area and surface chemistry on the model system. In particular, we focus of the storage modulus, the length of the linear viscoelastic region and the rate of network breakdown after the linear region. We interpret these results in terms of hydrogen bonding between the silica aggregates and its role in reinforcing the fat crystal networks. Then, we study the time-dependent rheological behaviour of this system using the three interval thixotropy test. We measure the deformation under an applied stress and the recovery of structure once the applied stress is removed. We show that, under certain conditions, both fat and silica networks are thixotropic, leading to a full recovery after an applied deformation. We observe a synergistic effect leading to much stronger gel networks when fat and silica are present together. We use polarized light microscopy to gain a more direct insight into the effect of silica aggregates on the fat crystal microstructure. In particular, we study the effects of different fat concentrations, cooling rates, silica concentrations and silica surface chemistries. We use various image analysis techniques to quantify the fat crystal microstructure and find no significant difference in the presence of silica, at low concentrations.